1997
DOI: 10.1161/01.res.80.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenicity of IgG and Anti-52-kD SSA/Ro Affinity-Purified Antibodies From Mothers of Children With Congenital Heart Block

Abstract: An important advance in the description and understanding of congenital heart block (CHB) came in the 1970s with the observation that mothers of affected infants frequently had autoimmune diseases and, in particular, that many maternal sera contained antibodies to SSA/Ro and SSB/La ribonucleoproteins. Although the molecular biology of the candidate antigens has been extensively defined, the arrhythmogenic and electrophysiological effects of their cognate antibodies on the human fetal heart are unknown. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
132
1
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 43 publications
5
132
1
3
Order By: Relevance
“…The two sera that induced conduction blockade in these experiments were obtained from mothers with healthy infants. In contrast to our rabbit model, Boutjdir et al (1997) could only see AV conduction block or reduction in calcium currents in the human fetal hearts when using anti-52 kD affinity purified antibodies from mothers who had children with CHB. The reasons for this discrepancy are not immediately obvious, but we speculate that the target protein(s) at the cell membrane may not be 100% homologous in fetal human and adult rabbit hearts.…”
Section: Experimental Models For Nlecontrasting
confidence: 72%
See 1 more Smart Citation
“…The two sera that induced conduction blockade in these experiments were obtained from mothers with healthy infants. In contrast to our rabbit model, Boutjdir et al (1997) could only see AV conduction block or reduction in calcium currents in the human fetal hearts when using anti-52 kD affinity purified antibodies from mothers who had children with CHB. The reasons for this discrepancy are not immediately obvious, but we speculate that the target protein(s) at the cell membrane may not be 100% homologous in fetal human and adult rabbit hearts.…”
Section: Experimental Models For Nlecontrasting
confidence: 72%
“…The results in isolated ventricular myocytes correlated well with the observations at the whole heart level, since the conduction in the A-V node is basically dependent on calcium electrogenesis. Our results were later confirmed by Boutjdir et al (1997) using whole hearts and cardiac myocytes derived from human fetuses.…”
Section: Experimental Models For Nlesupporting
confidence: 69%
“…After preliminary reports, [11,12] Boutjdir in an outstanding paper [7] showed that IgG-enriched fractions and anti-52-kD SSA ⁄ Ro antibodies affinity-purified from the sera of mothers whose children have CHB reversibly induce complete atrioventricular (AV) block in the human foetal heart perfused by the Langendorff technique. At 33 min of perfusion, complete AV block was observed with the presence of only P waves and missing QRS complexes.…”
Section: Arrhythmogenicity and Electrophysiological Effects Of Anti-rmentioning
confidence: 99%
“…The other mechanism is the cross-reactivity of maternal antibodies with targets other than SSA ⁄ Ro and SSB ⁄ La antigens. Maternal antibodies were reported to cross-react with laminin and with human cardiac myosin heavy chain at a critical stage during foetal cardiac development [5,6], but the L-type calcium channels seem particularly important in this hypothesis [7][8][9][10].…”
mentioning
confidence: 97%
See 1 more Smart Citation